Ageing nestlings of the Reed Warbler Acrocephalus scirpaceus. Issue 1 (2nd January 2018) - Hałupka, Lucyna; Sztwiertnia, Hanna; Marczuk, Magdalena; Dziachan, Alicja; Kosmowska, Anna; Klimczuk, Ewelina; Halupka, Konrad
ABSTRACT: Proper ageing of the young birds is crucial in all studies examining age-related characteristics of nestlings and parental effort at the nestling stage. When nests are found after hatching, the age of nestlings cannot be calculated as a time interval from the hatching day: a species-specific guide is needed, but such guides are rarely published. This study describes the post-embryonal development of Reed Warbler nestlings and presents a guide to ageing nestlings of this species. The guide is based on measurements and observations of 354 nestlings of Reed Warblers from 107 nests found during two breeding seasons. We provide a description of developmental events by day, together with nestling drawings, photos and further tables of summarised data. All the traits showed huge variation among the nestlings of the same age, and day-to-day differences in trait values varied throughout the nestling period. We suggest using several traits while ageing this species' young, especially those that show the most rapid growth at a given stage of development. We also present a simple key to ageing this species' nestlings.